KEBUDAYAAN (TANI) JAWA SEBAGAI SUMBER NILAI EKOLOGI - Dhanu Priyo Prabowo (Jantra., 2019)
The Javanese farming culture and ecological values can be traced from various manuscripts. This paper aims to reveal the contribution of the Javanese farming culture to the Javanese ecological values. Considering their relation with nature, to preserve the ecological harmony the Javanese farmers provide lessons about ecological values. The tight relation between ecology and (natural) harmony is evidenced by the power of culture. The farmers perform the ecological and natural harmony through their rice cultivation. The unimaginable impact of Green Revolution has changed the paradigm of farming culture. The difficulty in eliminating rice field pests is one form of the revolution. The data sources of this paper were obtained from a number of Javanese manuscripts. Using eco-criticism approach, this study explains how the Javanese farming culture become the representation of nature which has influenced the life of farmers.